Coronary Sinus Ostial Atresia and Persistent Left-Sided Superior Vena Cava: Clinical Significance and Strategies for Cardiac Resynchronization Therapy - Lim, Paul Chun Yih; Baskaran, Lohendran; Ho, Kah Leng; Teo, Wee Siong; Ching, Chi Keong (International Journal of Angiology, 2013)
A 48-year-old male patient underwent cardiac resynchronization therapy defibrillator implantation, and he was found to have atresia of the coronary sinus ostium with venous drainage occurring via a persistent left-sided superior vena cava, which was connected to the right-sided superior vena cava by the innominate vein. This is a rare benign cardiac anomaly that can pose problems when the coronary sinus needs to be cannulated. To identify the course of the coronary sinus, a coronary angiogram can be performed with attention directed to the venous phase of the angiogram. Although the technical difficulty of coronary sinus cannulation increases, various catheters, wires, and delivery systems can be utilized and this anomaly does not usually prevent successful left ventricular lead placement in cardiac resynchronization therapy via a left-sided superior vena cava approach. There however needs to be consideration regarding caliber of the left-sided superior vena cava being sufficiently large to avoid compromise of venous drainage after lead insertion.
Keywords: coronary sinus; atresia; left-sided superior vena cava; CRT